Innovative Information Technology in Auditing: Auditors' Perceptions of Future Importance and Current Auditor Expertise. (4th May 2022) - Feliciano, Cristiano; Quick, Reiner
ABSTRACT: Innovative information technology (IT) could help to improve the effectiveness and efficiency of audits. Accordingly, we investigate the future importance, and current auditor expertise, regarding 18 technologies identified from a comprehensive literature review and interviews with Big 4 audit technology experts. We then surveyed German auditors and received 433 usable responses. Respondents perceive most of the analyzed IT as relevant in the next three to five years. Online meeting solutions and data mining have the highest importance rating. By contrast, self-assessed current personal knowledge of most IT is low. Complementary regression analyses reveal that female auditors and Big 4 auditors perceive IT as more important, and younger auditors and Big 4 auditors assess their own knowledge as higher. Comparing importance and knowledge ratings, we find a serious importance-knowledge gap for all considered IT. Intensive educational efforts seem to be essential in order to close this gap.